Selected issues regarding children’s rights in the war on terror with a particular focus on Syria - Matusiak-Frącczak Magdalena (Wroclaw Review of Law, Administration and Economics)
The aim of the article is to analyse the legal situation of the children held in camps in northeast Syria. The situation in the camps is devastating and poses a threat to the children’s right to life as well as physical and mental integrity. The article explores whether the states of citizenship of these children exercise any jurisdiction over them, and if the answer is affirmative, to what extent they exercise this jurisdiction. Next, the research will focus on the question of whether the states of citizenship have the obligation to repatriate those children from Syria. To this aim, the status of these children as victims of human trafficking will be also examined. Lastly, the deliberations will focus on the policy of citizenship revocation that is applied by some states in terrorism combatting and it will be studied whether this policy can be applied to children in conformity with international law. It results from the analysis that states have obligations towards children placed in the Syrian camps being their nationals, especially an obligation to repatriate them and to enable their rehabilitation and reintegration.